Assessing the morphology of nasopalatine canal in a subset of the Iranian population using cone beam computed tomography - Zahra Tafakhori; Azam Rooholamini (Mashhad University of Medical Sciences, 2023)
Objective: This study aimed to assess the shape and size of the nasopalatine canal (NPC) using cone beam computed tomography (CBCT) in Iranian patients.Materials and Methods: This cross-sectional descriptive study investigated 285 CBCT scans of the anterior maxilla, obtained from patients in Rafsanjan, Iran. The shape of the nasopalatine canal was categorized as banana (twisted), funnel (diverging towards the oral or nasal cavity), cylindrical, and hourglass. The length and diameter of the canal were measured using multiplanar images. Labial bone thickness was recorded at two points: A at the incisive foramen and B at the foramen of Stenson. Kruskal-Wallis and chi-square tests were used for analysis at P<0.05.Results: The hourglass shape was the dominant canal model in the sample. The mean canal length and the mesiodistal and labiopalatal diameter (at incisive foramen) were 11.17 ± 2.5 mm, 3.6 ± 1.2 mm, and 3.4 ± 1.2 mm, respectively. Moreover, the mean bone thickness at points A and B were 6 ± 1.4 and 8 ± 4.4 mm. A significant difference was found among different canal shapes concerning bone thickness at point B (P=0.01) and labiopalatal width of the canal (P<0.001). There was a direct and significant relationship between the patient's age and the mesiodistal and labiopalatal widths of the NPC (P=0.001 and P=0.015, respectively).Conclusion: Concerning the age-related and race-related variations in nasopalatine canal morphology, CBCT scans are recommended for accurate evaluation before implant placement or orthodontic retraction in the anterior maxilla.